2006
DOI: 10.1186/1471-2407-6-60
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronic acid treatment impairs protein geranyl-geranylation for biological effects in prostatic cells

Abstract: Background: Nitrogen-containing bisphosphonates (N-BPs) have been designed to inhibit osteoclast-mediated bone resorption. However, it is now accepted that part of their anti-tumor activities is related to interference with the mevalonate pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
65
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 29 publications
6
65
0
Order By: Relevance
“…However, with respect to the in vitro effects of ZOL on prostate cancer cells, inhibition of geranylgeranylation seems to be more critical than the inhibition of farnesylation (34,35,44). Here, we have presented evidence that the synergistic action of SAHA and ZOL was also conferred through inhibiting geranylgeranylation rather than farnesylation.…”
Section: Discussionmentioning
confidence: 80%
“…However, with respect to the in vitro effects of ZOL on prostate cancer cells, inhibition of geranylgeranylation seems to be more critical than the inhibition of farnesylation (34,35,44). Here, we have presented evidence that the synergistic action of SAHA and ZOL was also conferred through inhibiting geranylgeranylation rather than farnesylation.…”
Section: Discussionmentioning
confidence: 80%
“…IPP is further metabolized endogenously into an ATP analogue ApppI, which is able to induce apoptosis in cells by inhibiting mitochondrial adenine nucleotide translocase (ANT), causing also a loss of the mitochondrial membrane potential [17,20]. Several studies have demonstrated that the interruption of the protein prenylation is a major contributor to the anticancer action of N-BPs [7,36,37], whereas the role and the significance of the additional mechanism of action, accumulation of IPP/ApppI, is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…HMGR is controlled by negative feedback overcome statin and N-BP-induced apoptosis in many cell types [7,8,15,16,27,28]. In addition, we have evidence that GGOH may possess the capacity to inhibit ZOLinduced IPP/ApppI formation in tumor cells [20], but the mechanism underlying this effect is not known.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Bisphosphonates (Fig. 2B), which have been used to treat osteoporosis and similar diseases in millions of people (25), have been shown to be efficient FPPS (26) and, in some cases, GGPPS (27) inhibitors, and one approach for the development of drugs for neglected diseases is the repositioning of drugs currently in use (28). Bisphosphonates have also been found to be active against a variety of protozoan parasites, for example, Trypanosoma brucei, Trypanosoma cruzi, Leishmania donovani (26,(29)(30)(31), Cryptosporidium parvum (32), Entamoeba histolytica (33), Toxoplasma gondii (34), and Plasmodium species (26,33,(35)(36)(37).…”
mentioning
confidence: 99%